How anxiety attributed to COVID-19, disease knowledge, and intention to vaccinate against SARS-CoV-2 viral infection prevail in general public of Saudi Arabia? - Islam, Md. Ashraful; Alshayban, Dhfer Mahdi; Naqvi, Atta Abbas; Maqsood, Muhammad Bilal; Ishaqui, Azfar Athar; Kashif, Muhammad; Ali, Majid; Haseeb, Abdul (Frontiers in Public Health, 2023)
Aim The study aimed to document the anxiety attributed to COVID-19, disease knowledge, and intention to vaccinate against the disease among general public. Moreover, the interplay among these three outcomes was also investigated. Methods A cross-sectional study was conducted for 2 months in three cities of Dammam Region of Saudi Arabia. The target segment was the adult population of Saudi Arabia. Convenience sampling was used and all adults aged ≥ 18 were invited to participate. The questionnaire used in the study was available in both Arabic and English languages. It included a demographic section, a section dedicated to vaccination intention and, a section containing coronavirus anxiety scale (CAS). The data analysis was carried out using IBM SPSS version 23. The study was approved by an ethics committee (#IRB-2021-05-297). Results A total of 542 responses were analyzed. Most respondents had no anxiety attributed to COVID – 19 (92.1%), self-reported good knowledge of COVID-19 (79.7%) and intended to administer a vaccine (57.4%). Age groups 18-29 years and 30-45 years, and having a chronic medical condition, were found to be determinants of having disease anxiety (p<0.05). The variables of self-rated good knowledge of disease, never contracted COVID-19, and incomes of SAR 5,000 (i.e., USD 1333), and SAR 7,500 – 10,000 (i.e., USD 1999.5 – 2666), were found to be determinants of having positive intention towards vaccination (p<0.05). Conclusion The anxiety due to COVID-19 disease was present in a few participants. Besides, self-reported knowledge about COVID-19 and intention to administer a vaccine, were positively linked to each other. However, both variables had no effect on disease anxiety. It is important to review and address the determinants of positive intention to further increase vaccine acceptance rate.